Counter-hegemonic pedagogy: Activism and the life of the organic intellectual - Mervin E Chisholm (Adult Education Research Conference, 2023)
The continuing search for counter-hegemonic pedagogy is underscored. Aspects of the search are brought into the conversation and useful approaches for advancing emancipatory pedagogy are offered and discussed.
Keywords: counter-hegemonic; pedagogy; pedagogical activism; organic-intellectual